Targeting Impaired Antimicrobial Immunity in the Brain for the Treatment of Alzheimer’s Disease - Fulop, Tamas; Tripathi, Shreyansh; Rodrigues, Serafim; Desroches, Mathieu; Bunt, Ton; Eiser, Arnold; Bernier, Francois; Beauregard, Pascale B; Barron, Annelise E; Khalil, Abdelouahed; Plotka, Adam; Hirokawa, Katsuiku; et al. (Neuropsychiatric disease and treatment, 2021)
Alzheimer's disease (AD) is the most common form of dementia and aging is the most common risk factor for developing the disease. The etiology of AD is not known but AD may be considered as a clinical syndrome with multiple causal pathways contributing to it. The amyloid cascade hypothesis, claiming that excess production or reduced clearance of amyloid-beta (Aβ) and its aggregation into amyloid plaques, was accepted for a long time as the main cause of AD. However, many studies showed that Aβ is a frequent consequence of many challenges/pathologic processes occurring in the brain for decades. A key factor, sustained by experimental data, is that low-grade infection leading to production and deposition of Aβ, which has antimicrobial activity, precedes the development of clinically apparent AD. This infection is chronic, low grade, largely clinically silent for decades because of a nearly efficient antimicrobial immune response in the brain. A chronic inflammatory state is induced that results in neurodegeneration. Interventions that appear to prevent, retard or mitigate the development of AD also appear to modify the disease. In this review, we conceptualize further that the changes in the brain antimicrobial immune response during aging and especially in AD sufferers serve as a foundation that could lead to improved treatment strategies for preventing or decreasing the progression of AD in a disease-modifying treatment.